2021
DOI: 10.3390/en14227721
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MOCVD-Prepared CIS Solar Cells

Abstract: Chalcopyrite Cu(In,Ga)Se2 (CIGS) solar cells prepared via metal-organic chemical vapor deposition (MOCVD) are one of the candidates for highly advanced photovoltaic devices. This is because of their effectiveness and potential for reducing production costs through large-scale production. However, research on MOCVD-prepared solar cells is progressing slower than that on other types of solar cells, primarily because the preparation of CuInSe2 (CIS)-based films via MOCVD is relatively more sophisticated. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…In conclusion, the articles in this Special Issue show the latest progress achieved in renewable energy technologies, especially regarding solar cells. There is no doubt that these articles [1][2][3][4] present exciting and significant research results, as well as make contributions to renewable energy research fields, allowing us to take another step toward achieving a zero-carbon society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the articles in this Special Issue show the latest progress achieved in renewable energy technologies, especially regarding solar cells. There is no doubt that these articles [1][2][3][4] present exciting and significant research results, as well as make contributions to renewable energy research fields, allowing us to take another step toward achieving a zero-carbon society.…”
Section: Discussionmentioning
confidence: 99%
“…Seung Hoon Lee et al [2] demonstrated detailed methods and results from an analysis of CIS solar cells, which are prepared by unique and advanced technology, the metal-organic chemical vapor deposition (MOCVD) method. Additionally, these authors demonstrated the use of highly efficient CIS solar cells without applying a buffer layer, achieving a 7.39% power conversion efficiency.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%